Pengaruh Human Capital dan Structural Capital Terhadap Kinerja Keuangan Perusahaan Perbankan Konvensional - Aldi Riady; Radja, Muh. Jusuf; Muchtar, Hasyim (Insan Cita Bongaya Research Journal, 2024)
The purpose of this study is to analyze the effect of human capital and structural capital on the financial performance of conventional banking companies listed on the Indonesia Stock Exchange with an observation period of 2019-2021. To achieve this goal, data collection techniques are used through documentation obtained through the website www.idx.co.id. Data analysis techniques used descriptive analysis, classical assumption test, multiple regression analysis and hypothesis testing. The results of the study found that human capital (VAHU) had a positive and significant effect on financial performance (ROA). Meanwhile, structural capital has a negative and insignificant effect on financial performance (ROA) in Conventional Banking companies listed on the Indonesia Stock Exchange for the period 2019 to 2021